Composite Indicator for Measuring the World Interest by Portugal’s Tourism - Dinis, Gorete; Costa, Carlos; Pacheco, Osvaldo (Journal of Tourism, Sustainability and Well-being, 2019)
Tourism is a phenomenon with unique characteristics and particularities, which makes its measurement difficult. The rapid changes in society and consumer behaviour associated with the countries’ economic situation have made the collection of statistical data difficult, impacting on the dissemination of updated and relevant indicators. This fact evidences the difficulty in having timely knowledge of the sector and consequently the tourism stakeholder’s hard and imprecise decision-making. The Internet has proved to be an important source of data, and it is possible, through tools like Google Trends (GT), to know timely the interests and intentions of potential consumers in tourism. The objective of this paper is to present a methodology for building a composite indicator to measure the world interest of Portugal as a tourist destination. The composite indicator is conceptually based on the classification of activities and products’ characteristics of tourism that are part of the proposed tourism supply defined in the Tourism Satellite Accounts (TSA). Primary indicators were collected over a year using GT and weighted with indicators of total tourist consumption in Portugal. Our findings indicate that the interest of Internet users worldwide by tourism in Portugal varies throughout the year and the interest of search differs according to the tourism product characteristics.